Factors Associated with Malnutrition among Newly Diagnosed Esophageal Cancer Patients - Yi, Ho Chiou; Kahairudin, Zuliehaiza; Musa, Aini; Mohd Haniff Lai, Betti Sharina; Kay, Neoh May; Han, Ng Wai; Zakaria, Nor Adlina; Mohd Samwil, Siti Nuraini; Abdullah, Aeininhayatey; Pardi, Munawara; Jamhuri, Norshariza (Jurnal Gizi dan Pangan, 2025)
The study aimed to investigate the factors associated with malnutrition among newly diagnosed EC patients. A cross-sectional study included newly diagnosed EC patients from October 2020 to March 2022. Data on clinical status (diagnosis, comorbidities, and cancer stage), socio-demographic characteristics, functional status [Performance status scale using Eastern Cooperative Oncology Group (ECOG)], anthropometric measures [weight, height, and percentage of weight loss (% LOW) past 1-month], biochemical profiles [lymphocyte and serum albumin], malnutrition status [Subjective Global Assessment (SGA)] and total daily energy protein intake were assessed. The study enrolled 227 participants, and 96.5% (n=219) were malnourished. The mean for age, weight, percentage of weight loss past 6-months, SGA score, total daily energy protein intake, and serum albumin were 61.1±11.4 years, 57.7±14.4 kg, -8.6±6.5%, 12.6±3.9, 17±5 kcal/kg/day, 0.7±0.1 g/kg/day, and 35±5 g/L respectively. About 80.6% were stage III and IV, 96% experienced dysphagia, and 67% experienced muscle wasting. The % LOW past 1 month, gender, ECOG status, and lymphocyte levels were found to be the significant factors related to malnutrition among newly diagnosed EC patients (p<0.05) by a multi-linear regression test. EC patients are at high risk of being malnourished as the tumor-related symptoms include dysphagia, inadequate nutritional intake, muscle wasting, and lymphocytopenia. The current study is restricted to only one-time nutritional screening and evaluation. The current proposed model of malnutrition is a simple, useful, and efficient clinical tool to identify EC-related malnutrition followed by the early multidisciplinary-team approach-based nutrition intervention to minimize nutrition depletion, improve functional status, and enhance clinical outcomes before therapy or even higher survival rate.